Study of the Side Effects of Pfizer and Oxford COVID-19 Vaccines in the Eastern Province of Saudi Arabia - Farhat M; Al-Ibrahim R; Almohammedali A; Aljishi R; Alalwan B (International Journal of General Medicine, 2022)
Maha Farhat,1 Rabab Al-Ibrahim,2 Abrar Almohammedali,2 Roaa Aljishi,2 Baneen Alalwan2 1Department of Biochemistry, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Maha Farhat, Department of Biochemistry, Faculty of Medicine, Imam AbdulRahman Bin Faisal University, King Faisal Ibn Abd Al Aziz, King Faysal University, Dammam, 34212, Saudi Arabia, Tel +966 507107411, Email mFarhat@iau.edu.saBackground & Objective: The COVID-19 pandemic imposed global concern and became one of the deadliest pandemics of the twenty-first century. Several vaccines were developed against SARS-CoV-2 to counteract the effects of this virus. This study aims to determine the post-vaccination side effects of the most common COVID-19 vaccines used in the Eastern province of Saudi Arabia.Methods: This is a cross-sectional study using an online questionnaire distributed randomly through social media. Frequencies were calculated to determine participants’ demographic information, vaccination details, and post-vaccination side effects. Univariate and multiple regression analysis were applied to test the association between individuals’ willingness to receive a booster dose and different categorical variables.Results: A total of 1004 participants were included in the survey, of which 0.6%, 85.3% and 14.1% completed either one, two or three doses of the Pfizer mRNA vaccine and Oxford AstraZeneca vaccines, respectively. The similar common side effects between the first and the second doses were significantly associated with the type of vaccine received; these included fatigue (Pfizer 54.4%, Oxford 73.2%; p < 0.001), headache (Pfizer 33.2%, Oxford 44.7%; p = 0.002), and fever (Pfizer 25.1%, Oxford 57.6%; p < 0.001). Additionally, unusual side effects were also reported (palpitations and menstrual abnormalities). Getting SARS-CoV2 infection after vaccination was significantly associated with the type of vaccine received at the first dose (Chi-Square=5.496, p = 0.019). A statistically significant association was found between the individuals’ willingness to receive a booster dose and their gender (Chi-Square = 39.493, p < 0.001), age (Chi-Square = 11.668, p = 0.02), presence of allergies (Chi-Square = 5.602, p = 0.018), and previous COVID-19 infection (Chi-Square = 9.495, p = 0.002).Conclusion: Despite the described side effects, further studies should be done to investigate the unusual and rare side effects to assess COVID-19 vaccines effectiveness and safety over longer period of time within a more diverse population.Keywords: SARS-CoV-2, Pfizer-BioNTech vaccine, Oxford-AstraZeneca vaccine, side effects